If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3 + -4n) = 12n + -19 (3 * 7 + -4n * 7) = 12n + -19 (21 + -28n) = 12n + -19 Reorder the terms: 21 + -28n = -19 + 12n Solving 21 + -28n = -19 + 12n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-12n' to each side of the equation. 21 + -28n + -12n = -19 + 12n + -12n Combine like terms: -28n + -12n = -40n 21 + -40n = -19 + 12n + -12n Combine like terms: 12n + -12n = 0 21 + -40n = -19 + 0 21 + -40n = -19 Add '-21' to each side of the equation. 21 + -21 + -40n = -19 + -21 Combine like terms: 21 + -21 = 0 0 + -40n = -19 + -21 -40n = -19 + -21 Combine like terms: -19 + -21 = -40 -40n = -40 Divide each side by '-40'. n = 1 Simplifying n = 1
| 6y-4(y-1)+3= | | 2x+3-7x=28 | | 4x=11+1 | | 2.2k-4.3=12.6k+14.5 | | 3x+5-x=x+5 | | 2a+6+3a=16 | | 4x+33+6x+5=360 | | 4(5x+1)+4(x-3)= | | 11x-19y=-7 | | 7y-21=-8y | | 4x=3+10 | | 2(x+3)=18-6x | | v^3+8=0 | | 90x-1.5x^2=1200000 | | 2.2x+0.4=2(1.1x-0.1) | | 14x+6+10x+6=180 | | 7y+21=-8y | | 25x^2-95x+61=0 | | 2+7x=20x | | 3x-3*x-3=2x-1*2x-1*2x | | -5x-(6x-3)=-8x+27 | | -t+47282=4848235 | | -8(1-7n)-1=-9+8n | | 7x-15=11+5x | | -10c=-40 | | 7x+9x=20 | | -42x-6=42x+7+6 | | 3/7=p-1/7 | | 60a^3b-52a^2b+8ab= | | 9x+8=6x+7 | | 10-10x=23-17 | | 16x^2+40x+16=-9 |